A case of adult-onset tubulointerstitial nephritis and uveitis syndrome presenting with granulomatous panuveitis - Kemal Tekin; Yasemin Ozdamar Erol; Olcay Kurtulan; Dilek Ertoy Baydar (Taiwan Journal of Ophthalmology, 2020)
The tubulointerstitial nephritis and uveitis (TINU) syndrome is a rare disorder that is probably underdiagnosed in clinical practice. Ocular involvement in TINU syndrome not only presents with the nongranulomatous anterior uveitis in 80% of patients but also manifests as intermediate, posterior, or panuveitis. This case report mentions an adult male patient who presented with granulomatous iridocyclitis with panuveitis and mild renal insufficiency. Workup for connective tissue and infectious diseases was negative for the patient. He was diagnosed with TINU syndrome based on the findings of renal biopsy. Both the uveitis and nephritis promptly responded well to steroid treatment, and there was no recurrence during the follow-up of 24 months.